Analysis and management algorithm of complex security based on cognitive modeling - Козловський, Валерій Валерійович; Міщенко, Андрій Віталійович; Сніжко, В’ячеслав Володимирович (Technology audit and production reserves, 2014)
The features of information security system creation, taking into account the subjective side of the process are analyzed in the article. The main aim of investigation is algorithm developing of analysis and management of integrated security, which will unify approaches to information security management. Security does not exist in itself, apart from person. It provided for a person and it is estimated by person. Therefore, the concept of security is not only objective, but also subjective side, because of its evaluation is carried out in the end by person. Use of cognitive modeling can significantly improve the processes of analysis and safety management of information system. Benefits of cognitive approach is the possibility of semi-structured system modeling (bad formalized), which are characterized by incomplete or uncertain information about them. Algorithm application will allow experts in the field of information security begin to develop appropriate computational procedures and modules that can be further used in the construction of information security systems. Investigation results will be useful for services that deal with information security.